Kastamonu İlinde Kullanılan Betonların Nicel Analizi - Memi̇ş, Selçuk; Yilmazoğlu, Mehmet Uğur; Mütevelli̇, İffet Gamze (Düzce University, 2015)
Depending on the increase in Kastamonu population, in the number of plants, projects and structures is rapidly increasing. The city center is the first of the earthquake zone in quake map which prepared Turkey Earthquake Zones that prepared by the Ministry of Public Works and Settlement at 1997. North Anatolian Fault in this region passes through the city center, about 70 km from Tosya county. The performance of concrete to be used that structures and facilities to be made in areas with high seismic risk must be high. In this study, compressive strength of concrete that made structures and facilities used in Kastamonu province between the years of 2008- 2013 are examined statistically. Quality of the concrete used in the region is determined by the years and the concrete class. Also this study was demonstrated the variability of the concrete compressive strength.

Kastamonu’da nüfusunun artmasına bağlı olarak yapılan projelerin, tesislerin, konut yapılarının sayıları hızla artmaktadır. İl merkezi 1997’de Bayındırlık ve İskan Bakanlığı’nca hazırlanan Türkiye Deprem Bölgeleri Haritası’nda 1.dereceden deprem bölgesidir ve Kuzey Anadolu Fayı İl merkezine yaklaşık 70 km uzaklıktaki Tosya İlçe’sinden geçmektedir. Deprem riski bakımından yüksek olan bölgede yapılacak yapı ve tesislerde kullanılacak betonun performansı yüksek olmak zorundadır. Bu çalışmada Kastamonu İli’nde 2008-2013 yılları arasında yapılmış yapı ve tesislerde kullanılan betonların basınç dayanımları istatiksel olarak incelenmiştir. Bölgede kullanılan betonların niteliği yıllara ve beton sınıfına göre belirlenerek, beton basınç dayanımındaki değişkenlikler ortaya konmuştur.
Keywords: beton kalitesi; concrete quality; Technology; kastamonu; Science (General); T; Science; basınç dayanımı; Q; Mühendislik; Kastamonu; Concrete quality; Compressive strength; compressive strength; Engineering (General). Civil engineering (General); Q1-390; Engineering; TA1-2040; Kastamonu; Beton kalitesi; Basınç dayanımı; 11. Sustainability